Multiple Representations Appear When Students Interpret Signs in Constructing Rectangle Concepts - Suryaningrum, Christine Wulandari; Lestari, Rr. Putri Hawa Dwi (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Multiple Representation the ability to use several mathematical expressions. The purpose of this study is to describe the representations that appear when students interpret the signs. Descriptive explorative research is used in this study with three elementary school students in the Jember Regency. The research was conducted teacher’s teaching process, recording students 'activities using field note sheets, and analyszing the results of students' notes when constructing concepts. The research findings showed that the subject interpreted the sign by investigating the sign and then using some interpretations to express his mathematical ideas in the form of writing, pictures, tables, numbers, and symbols. This shows when interpreting the subject's sign using multiple representations. The representations used are image, verbal, and symbol representations. The results of this study are useful for teachers to stimulate children to make more than one representation when constructing a rectangle concept.